Pharmacist Role in Hypertension Management in the Community Setting: Questionnaire Development, Validation, and Application - Lama Soubra (11666333) (2023)
Background Hypertension is a leading cause of mortality and morbidity globally. Pharmacists can play a substantial role in decreasing the burden of the disease. Purpose The primary aim of this study was to develop and validate a scale assessing the pharmacist role in hypertension management in the community pharmacy setting. The secondary aims were to assess the services/interventions in hypertension management that were performed in the real-life setting, as well as the patient satisfaction from these services/interventions. Methods This cross-sectional study was conducted in Egypt. The data were collected using a survey composed of three sections: a general section, the pharmacist role questionnaire section, and the patient satisfaction from the provided interventions/services section. The pharmacist role questionnaire was developed based on the pharmaceutical care practice conceptual model and included 23 questions. The face validity, content validity, reliability testing using Cronbach alpha, and construct validity using exploratory factor analysis were determined. The percentage of the frequency by which each role was reported to be performed was determined. Patient satisfaction from the provided interventions/services was determined by means of an overall rating. The correlation between practiced roles and patient satisfaction with received interventions/services was determined. Results The questionnaire was valid with a 4-factor structure and a Cronbach alpha > 0.75, reiterating the main pharmaceutical care practice domains: medication management, disease-state education, disease-state management, and care plan monitoring. Roles falling in the domains of disease state management and disease state education were significantly more practiced than roles falling in the other domains. Conclusion Pharmacist practice in hypertension management in the community setting was inclined towards contemporary roles, such as disease state education and management. Patients seem to be satisfied with these roles. Other Information Published in: Patient Preference and Adherence License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/ppa.s394855